2009
DOI: 10.1007/s10514-009-9134-y
|View full text |Cite
|
Sign up to set email alerts
|

Online world modeling and path planning for an unmanned helicopter

Abstract: Mission scenarios beyond line of sight or with limited ground control station access require capabilities for autonomous safe navigation and necessitate a continuous extension of existing and potentially outdated information about obstacles. The presented approach is a novel synthesis of techniques for 3D environment perception and global path planning. A locally bounded sensor fusion approach is used to extract sparse obstacles for global incremental path planning in an anytime fashion. During the flight, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Whereas this work focuses on software verification and certification issues, a general overview about ARTIS can be found in [43], where the following onboard software components and functionalities for decisional autonomy are also summarized: 1) payload-directed mission elements (vision-based gate passing and vision-based ground vehicle tracking) [44], 2) real-time world modeling and path replanning [45,46], 3) online exploration behavior in urban terrain [47] (Fig. 2), 4) usage of a large urban terrain database (city of Berlin) [48], 5) composite flight behaviors that solve abstract guidance tasks (search pattern planning and safe perimeter tracking) [49], 6) trajectory following of linear segments and cubic splines [50], and 7) evaluation of the roadmap-based path planning (performance, smoothness, and safety) [51] (Fig.…”
Section: Artis Uav Fleetmentioning
confidence: 99%
“…Whereas this work focuses on software verification and certification issues, a general overview about ARTIS can be found in [43], where the following onboard software components and functionalities for decisional autonomy are also summarized: 1) payload-directed mission elements (vision-based gate passing and vision-based ground vehicle tracking) [44], 2) real-time world modeling and path replanning [45,46], 3) online exploration behavior in urban terrain [47] (Fig. 2), 4) usage of a large urban terrain database (city of Berlin) [48], 5) composite flight behaviors that solve abstract guidance tasks (search pattern planning and safe perimeter tracking) [49], 6) trajectory following of linear segments and cubic splines [50], and 7) evaluation of the roadmap-based path planning (performance, smoothness, and safety) [51] (Fig.…”
Section: Artis Uav Fleetmentioning
confidence: 99%
“…Although many papers have been published on vision‐based obstacle avoidance for rotorcraft, very few systems have been implemented on an actual aircraft, and modest experimental results have been reported in the literature. In Andert and Adolf (), stereo vision has been used to build a world representation that combines occupancy grids and polygonal features. Experimental results on mapping are presented in the paper, but there are no results about path planning and obstacle avoidance.…”
Section: Related Workmentioning
confidence: 99%
“…Note that this sensor model does not reduce the occupancy probabilities in proportion to range squared, which would be a more accurate representation of stereo error characteristics (Andert & Adolf, 2009; Matthies & Shafer, 1987). An evaluation of the proposed stereo model and the one of (Andert & Adolf, 2009) was conducted and showed that incorporating the Gaussian error properties does not improve the results when large voxels are used (such as the 0.5‐m voxels we use). Because the resulting map is discretized at a coarse resolution, the extra fidelity offered by a Gaussian error model is lost.…”
Section: Three‐dimensional Occupancy Mappingmentioning
confidence: 99%